Sector Risk Measurement During COVID-19 Pandemic - Zbigniew KORZEB; Paweł NIEDZIÓŁKA (Communications of International Proceedings, 2021)
COVID-19 forced a change in the model of risk management in financial institutions, one of the reasons for which turned out to be bringing to the fore the risk associated with the individual sector of the economy represented by issuers, borrowers or insured entities. The purpose of this research is to propose a new tool that will enable the measurement of sector risk and the prioritization of industries in terms of risk. The research was based on data of 11 economic sectors according to the NACE 2 classification. Sectoral data included 200 stock market indices from 13 EU countries, GVA, employment and PMI. Using 6 methods of linear ordering and 2 different weighting systems, the risk classification of individual sectors of the economy was determined. The advantage of the proposed method of assessing the sector risk is the reference to the current eco-financial situation of the sector, which is reflected in the behaviour of sector indices. At the same time, the basic parameters describing the latest prosperity of the sector (GVA and employment) are not omitted. The method also includes a forecasting component, to some extent taking into account market expectations and sentiment. It is the PMI index. The proposed solutions applied in the study can be used to a wide extent, as a tool supporting credit, insurance and investment decisions. The method enables dynamic management of sector risk, the volatility of which is influenced by lockdowns announced with different frequency for particular industries.
Keywords: COVID-19; Concentration Risk; Credit Risk; Sector Risk; Multi-Dimensional Comparative Analysis.